Model for Determining the Cost of Goods Manufactured of Copra in Pelambane Village - Annadya Tewu; Mahdalena; Amir Lukum (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze how the Activity-Based Costing (ABC) perspective helps identify costs that have not been accounted for in the practice of determining the cost of goods sold (COGS) for copra by farmers in Pelambane Village, Randangan Subdistrict, Pohuwato Regency. This study employs a qualitative method with a descriptive approach. Data were collected through in-depth interviews, observations, and documentation involving seven copra farmer informants selected using purposive sampling. Data analysis followed the interactive model of Miles and Huberman (1984), consisting of data reduction, data presentation, and drawing conclusions. The results of the study indicate that farmers construct the meaning of costs based on their daily economic experiences, equating costs with cash expenditures during the production process. Consequently, certain economic sacrifices—such as family labor, raw materials from one’s own garden, the use of long-term productive assets, and coconut husks as fuel—are not fully recognized as production costs. Through the ABC perspective, hidden costs were successfully identified across various production activities, revealing undercosting patterns that could potentially lead to illusory profits. This study contributes to the cost accounting literature by demonstrating that in informal agricultural enterprises, the concept of cost is shaped not only by economic rationality but also by social constructs, family culture, and production practices passed down through generations.